The legacy of haemophilia: Memories and reflections from three survivors. Issue 5 (19th May 2022) - Farrugia, Albert; Smit, Cees; Buzzi, Andrea
Abstract: Following the publication of a book of personal memories by one of us (CS 1, 2 ), we have attempted to synthesis our joint memories of three ageing men, born in the era preceding universal access to treatment, in an attempt to describe our experience, our challenges and our reflections on the development of therapies, which have ensured that our experience of growing up with haemophilia in the 1950s and 1960s has not been mirrored by the current generation of patients. We describe our upbringing in different parts of Europe in health care systems which, while of varying standards, were all unable to offer the kind of care which developed after the development of specific therapies. We assess the effect of the contamination of these therapies by blood‐borne pathogens on our own development, and the development of our communities around us. In addition, we reflect on the lessons learnt, sometimes painfully, by our generation of people with haemophilia and how some of these enabled us to overcome substantial hurdles, survive and build productive lives. Finally, we survey the development of therapies in the past 20 years, and offer some reflections on how our experience can be integrated in a realistic expectation of what the future holds for our community, in our own affluent societies and in countries less advantaged economically. We hope that our thoughts may contribute to continued progress in the field of haemophilia care.